Evaluation of Added Sugar and Sugar-Sweetened Beverage Consumption by University Students - Meric, Çağdaş Salih; Ayhan, Nurcan Yabanci; Yilmaz, Hacı Ömer (UI Scholars Hub, 2021)
Today, increased intake of sugar and sugar-sweetened beverages is seen today as an important factor in the growing prevalence of chronic diseases, such as obesity, obesity-related diabetes, and coronary heart diseases. This study involved 214 university students from the Department of Nutrition and Dietetics of Ankara University, Faculty of Health Science, which was intended to evaluate the consumption of sugar and sugar-sweetened beverages. The frequency of student consumption of beverages and the quantities and amounts of sugar taken with beverages were questioned. The average total amount of sugar added to drinks by the students was 4.69 ± 6.35 gram, while the average total amount of sugar taken with sugar-sweetened beverages was 11.34 ± 15.32 gram. Female students relative to male students, students in grade 4 compared to grades 2 and 3, and students who had daily breakfast compared to those who did not had lower average sugar consumption (p-value < 0.05). As class grades increase, the amount of sugar added to beverages and fruit juice and sweetened soft drinks and carbonated beverages decreased (p-value < 0.05). The consumption of herbal teas and dietary beverages increased and eating habits of students generally changed positively (p-value > 0.05). It is important to educate university students about the reduction in sugar intake and sugar-containing food in order to avoid many chronic diseases that may be seen in older ages.